2022
DOI: 10.1101/2022.03.04.22271003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-Ancestry Investigation of Venous Thromboembolism Genomic Predictors

Abstract: Venous thromboembolism (VTE) is a complex disease with environmental and genetic determinants. We present new cross-ancestry meta-analyzed genome-wide association study (GWAS) results from 30 studies, with replication of novel loci and their characterization through in silico genomic interrogations. In our initial genetic discovery effort that included 55,330 participants with VTE (47,822 European, 6,320 African, and 1,188 Hispanic ancestry), we identified 48 novel associations of which 34 replicated after co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 98 publications
(107 reference statements)
2
6
0
Order By: Relevance
“…Figure 3 displays the Manhattan plots of these results. In line with previous studies, 3-6,15,16 we identified ABO gene and FUT2 gene, which contributed to both VTE and COVID-19. Notably, we identified seven novel genes which have not been reported yet, including LINC00970 , and six protein-coding genes ( TSPAN15, ADAMTS13, F5, DNAJB4, SLC39A8 and OBSCN) .…”
Section: Resultssupporting
confidence: 92%
“…Figure 3 displays the Manhattan plots of these results. In line with previous studies, 3-6,15,16 we identified ABO gene and FUT2 gene, which contributed to both VTE and COVID-19. Notably, we identified seven novel genes which have not been reported yet, including LINC00970 , and six protein-coding genes ( TSPAN15, ADAMTS13, F5, DNAJB4, SLC39A8 and OBSCN) .…”
Section: Resultssupporting
confidence: 92%
“…The rs10737681 we identify with genome wide association with CFHR5 levels maps between the CFHR4 and CFHR1 genes (Figure 4B). Of note, the CFHR2 locus has just been identified as a novel susceptibility locus for VTE in the recently published international effort on VTE genetics [21]. The lead SNP at this locus is rs143410348, which is in moderate LD with the rs10737681 (r 2 = 0.38 in FARIVE) that here we found associated with CFHR5 plasma levels.…”
Section: Discussionsupporting
confidence: 50%
“…Risk scores based on clinical risk factors and D-dimer levels have been developed for recurrence prediction [12][13][14][15][16][17][18], but none are routinely integrated into clinical practice. In addition to the genetic variants currently used in clinical assessment of hereditary thrombophilia (e.g., Factor V Leiden, prothrombin mutation) there are other more recently discovered common gene variants that contribute to VTE risk [19][20][21]. However, even when these are also incorporated into risk scores, they still lack sufficient precision for VTE prediction on an individual basis [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Second, even though 257 cardiovascular and metabolic proteins were included in the analysis, the study by no means examined all circulating proteins in relation to VTE, which indicated that other important VTE-related proteins might be overlooked. 58 Third, compared to mass spectrometry methods, the Olink protein immunoassay was not able to profile different protein isoforms or posttranslational modifications. However, this method with moderate-tohigh specificity and high throughput efficiently measured the absolute quantifications of proteins in a large sample.…”
Section: Discussionmentioning
confidence: 99%